The Impact of Macroeconomic Policy on the Liquidity and Financial Stability of SMEs through the Prism of Banking Activities - Volodymyr Antoniuk; Maksym Marych (Облік і фінанси, 2025)
Unlike large companies, small and medium-sized enterprises (SMEs) are more sensitive to the influence of external factors, such as changes in market conditions, competition, and economic crises. Therefore, the development of such enterprises depends significantly on the state's macroeconomic policy and the availability of financing sources. The article aims to determine the impact of macroeconomic policy on the liquidity and financial stability of small and medium-sized enterprises through the prism of banking activities. The study uses a systematic approach to assess the relationship between macroeconomic factors and banking activities. In particular, statistical analysis was used to evaluate the dynamics of the main indicators of the financial stability of SMEs, and econometric modelling was used to determine the relationships between macroeconomic variables and the availability of credit resources. The article identifies the main macroeconomic factors that shape the availability of financing for SMEs, in particular: monetary policy (changes in the discount rate, inflation rate, banking regulation), fiscal policy (tax burden, government support programs), and the instability of the financial environment. The study results show that tight monetary policy, in particular an increase in the discount rate, significantly limits SMEs' access to credit resources, increasing the cost of borrowed capital and reducing the investment activity of enterprises. At the same time, fiscal policy, particularly the tax burden and state support programs, can compensate for monetary regulation's negative impact or create additional financial barriers for businesses. Countries with developed small business financing mechanisms, including tax incentives and flexible credit programs, demonstrate a higher level of SMEs' resilience to economic shocks. In addition, the level of financial literacy of entrepreneurs and their ability to adapt to changes in the economic environment remains an important factor. The results of the study provide recommendations for improving macroeconomic policy to ensure SMEs' financial stability.